Implementasi Sistem Rekomendasi dengan Content Based Filtering dan Teknologi Virtual Tour Untuk Strategi Pemasaran Pada Website - Insany, Gina Purnama; Somantri, Somantri; Amalia, Phina Putri (Building of Informatics, Technology and Science (BITS), 2024)
The real estate business is rapidly developing, supported by a stable economy and increased purchasing power of the public, which triggers intense competition in the property industry. Consequently, many companies are striving to offer modern solutions. Prospective buyers often struggle to choose a house that suits their needs due to the plethora of options, while real estate companies face challenges in providing attractive and comprehensive information. Solutions like a recommendation system with Content-Based Filtering and Virtual Tour technology offer innovative approaches that make it easier for consumers to select a house and enhance marketing strategies on the Setiabudi Land website. This recommendation system provides suggestions according to user characteristics and preferences with inputs such as age, marital status, number of children, monthly income, desired facilities, and environmental preferences. The output includes recommendations on the name of the housing complex, type, and model of the house. On the other hand, Virtual Tour offers a realistic visual experience, allowing consumers to view properties virtually without having to visit the physical location, showcasing the living room, family room, 2 bedrooms, 1 bathroom, and 1 kitchen. Evaluation results of the recommendation system's performance show accuracy, precision, recall, and F1-score levels in the range of 92-93%, while functionality tests of the Virtual Tour run smoothly. User Acceptance testing reached 88.66%, indicating a high level of user satisfaction with the recommendation system and virtual tour features.